DESKRIPSI GAYA BELAJAR SISWA BERPRESTASI - Adni Fitriyah; Mahmudah (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2019)
Students feel bored in some learning, due to learning to learn with a variety of methods. Furthermore, the learning styles of outstanding students are unknown, both by the teacher and his own students. The purpose of this study was to determine the learning style of student achievement. The research used purposive sample sampling technique. Techniques collected data with interviews. The analysis technique refers to Huberman and Miles, namely interactive models. Five results were obtained including energy auditing, three levels including visual learning and a minimum of energy included in the pharmacological samples.